Nutritional value of cane broth and nutraceutical potential of caná – cane broth´s fermented drink (Research, Society and Development, 2022)
Brazil is the world's largest producer of sugarcane, and its juice is used mainly for the production of sugar, fuel alcohol and industrial cachaça. To a lesser extent, thousands of producers cultivate sugarcane on a rural scale, for the production of alembic cachaça, brown sugar, rapadura and molasses. In recent years, however, these producers have been looking for options that, in addition to expanding the range of products, allow them to add more value to their properties and sugarcane fields. In this context, the feasibility of producing fermented sugarcane juice as a final drink, similar to grape wine, has been considered. The market potential of this beverage has been markedly expanded as a result of recent research, which proved the presence of phytoactive substances in sugarcane juice, such as apigenin, luteolin and asterine, among others. Continuing these works, which have already made it possible to scientifically support millenary practices related to the use of sugarcane juice in Ayuvedic medicine, is very important, both to reinforce the appreciation of sugarcane juice in the human diet, and to enable the classification of sugarcane - the fermented sugarcane of the emerging sugarcane juice in Brazil – as a beverage with functional activity, following the example of the recognition already won by wines that come from the fermentation of grape juice. To contribute in this direction, an update is presented in the scope of the chemical composition of the sugarcane juice, highlighting the main phytoactives already characterized.